Strategic Spirituality: Positive Psychology, the Army, and the Ambiguities of "Spirituality Fitness". (23rd April 2021) - Weitzman, Steven
Abstract: In the wake of increased mental health issues resulting from combat in Afghanistan and Iraq, psychologists affiliated with the field of positive psychology developed a resiliency training program for the US Army that included strengthening "spirituality fitness" as one of its goals. The initiative represents what may be the largest single effort to use spirituality to intervene in people's mental health, but it also represents an intervention in the semantics of spirituality, an attempt to make it signify in new ways. This study treats this intervention as an exercise in "strategic ambiguity, " the use of unclear language to balance between contradictory goals, and draws from this approach some inferences about what it is that those working in the field of positive psychology import into the spirituality they have promoted within American military culture.